Teniente Technology with Acid Plant Operation and Impurities Distribution at Las Ventanas Smelter - Sadi Medina (The Minerals, Metals and Materials Society, 1993)
As it is characteristic from Custom Smelters, ENAMl Las Ventanas Smelter has to deal with different qualities and quantities of mining products from about 70 suppliers, that contain a variety of impurities that would be harmful for copper production. In order to increase the smelting capacity, an oxygen plant has been running since September of 1990. Moreover, to improve the environmental conditions, a new sulphuric acid plant started up to neutralize the metallurgycal off-gases from the Teniente Converter and partially from the Peirce-Smith converters. Based on the on-line operation among the reverberatory furnace and the Teniente Converter using oxygen enriched air to produce high grade matte, most of the volatilizing impurities, mainly arsenic, are collected as discarding compounds in the gas cleaning system of the acid plant. This paper describes the continuous performance of the Teniente Converter with acid plant, the results attained, the operation problems and how they were solved. The impurities distribution achieved in this process is also included.